(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article delves into the critical subject of employee engagement, with dual objectives in mind. Firstly, it comprehensively explores the multifaceted concept of employee engagement, elucidating its emotional, cognitive, and behavioral dimensions, and underscores its significant role in the contemporary workplace. Second, the article meticulously identifies and discusses a spectrum of effective strategies aimed at bolstering employee engagement. From fostering open communication and transparent leadership to nurturing a culture of recognition, professional development, and work-life balance, this article offers a holistic view of the strategies that can catalyze higher levels of employee engagement. By illuminating the significance of engagement and presenting practical strategies, this article equips organizations with the knowledge necessary to develop a more motivated, dedicated, and productive workforce.